2015 IEEE Radio and Wireless Symposium (RWS) 2015
DOI: 10.1109/rws.2015.7129712
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-wave channel sounding of outdoor ground reflections

Abstract: A channel sounder for time variant channels is presented. A 60 GHz outdoor measurement campaign was conducted with focus on the properties of ground reflections over large distances up to 1000 m. A two-ray propagation model is introduced and compared to the measurement results in order to derive the ground reflection properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The two measurements show no meaningful difference; nonetheless, they nearly align with the theoretical model curve. It should be noted that open‐area measurements with a single horn antenna at 60 GHz were shown in and compared with those of the two‐ray model. In this study, we employed not a single antenna, but two different beamwidth antennas, and we experimentally showed that the two measurements were identical in an open area.…”
Section: Effects Of Directional‐antenna Beamwidth On Received Powermentioning
confidence: 99%
“…The two measurements show no meaningful difference; nonetheless, they nearly align with the theoretical model curve. It should be noted that open‐area measurements with a single horn antenna at 60 GHz were shown in and compared with those of the two‐ray model. In this study, we employed not a single antenna, but two different beamwidth antennas, and we experimentally showed that the two measurements were identical in an open area.…”
Section: Effects Of Directional‐antenna Beamwidth On Received Powermentioning
confidence: 99%
“…The other two events, acquired at the receiver position 21, show a counter intuitive behavior, as the path gain increases, when the cars are driving underneath the LOS path. The reason is flat fading, caused by a strong ground reflection as was shown in previous work [7]. With the given distance and antenna heights, a bandwidth much larger than the 250 MHz used here is necessary to resolve the flat fading.…”
Section: Observed Effectsmentioning
confidence: 68%
“…The two-ray model is a classic channel model that considers two major coexisting transmission paths, i.e., the light-ofsight (LOS) path and the reflection path, and the feasibility of modeling mm-wave channels has been investigated in [36]- [38]. The two-ray channel model is shown in Fig.…”
Section: A Two-ray Channelmentioning
confidence: 99%